Can the Scope of Secularization Theory Be Expanded Beyond the Modern-Christian-West? Exploring the Alevi Experience in Turkey - Ertit, Volkan (Journal for the scientific study of religion, 2024)
This study asserts that the secularization theory has the potential to offer insights into the processes of social change experienced by faith groups outside the modern West. The study focuses on the transformation undergone by Alevi groups in Turkey, who are now experiencing a more modern way of life compared to their past. In this qualitative study, data collection was conducted through semistructured interviews during field studies in the cities of Çorum (Turk Alevis) and Tunceli/Dersim (Zaza/Kurd Alevis). Based on the interview findings, the study concludes that the new Alevi generation leads a more modern and at the same time more secular daily life compared to their parents. Therefore, the main assertion of this research is that the classical secularization theory has the potential to provide valuable insights not only for modern societies where Christianity is dominant but also for understanding the transformations occurring within Alevi communities in Turkey.